Age-related and Epstein Barr virus-associated B-cell lymphoproliferative disorder: a 9-case report and literature review - Beltran Garate, Brady (2008)
Introduction: Age-related B-cell lymphoproliferative disorder associated with Epstein-Barr virus (EBV) is a newly described condition in our country. EBV infection may lead to a non-controlled growth of normally inactive B-lymphocytes, so lymphoproliferative disorders with an aggressive course and poor survival occur.Clinical cases: Nine Peruvian patients diagnosed with age-related B-cell lymphoproliferative disorder associated EBV were included in this report. All patients were positive for EBER test using chromogenic in situ hybridization (CISH). Morphology in every case corresponded to large-cell lymphoma. CD20, BCL6, CD10, and MUM-1/IRF4 histochemical expression was assessed using a tissue microarray. All nive patients had a phenotype not germinal center-like. Most of our patients were elderly subjects with a poor performance status, type B symptoms, high values in the International Prognostic Index (IPI) and advanced disease. Their survival was quite short.Conclusion: We report for the first time a new condition called age-related B-cell lymphoproliferative disorder associated EBV, which has an aggressive course and a poor prognosis.